Effects of age, cigarette smoking, and other factors on fertility: findings in a large prospective study. Issue 6483 (8th June 1985) - Howe, G; Westhoff, C; Vessey, M; Yeates, D
Abstract : Of 17 032 women taking part in the Oxford Family Planning Association contraceptive study, 4104 stopped using a birth control method to plan a pregnancy on a total of 6199 occasions. The influence of various factors on fertility in these women was assessed by measuring the time taken to give birth to a child. An appreciable inverse relation was observed between age at stopping contraception and fertility both in nulliparous and parous women, but the effect was much greater in the nulliparous women. The most important finding was a consistent and highly significant trend of decreasing fertility with increasing numbers of cigarettes smoked per day; it was estimated that five years after stopping contraception 10.7% of smokers smoking more than 20 cigarettes a day, but only 5.4% of non-smokers, remained undelivered. Some relation was found between fertility and social class, age at marriage, and a history of gynaecological disease, but weight, height, and Quetelet's index were without noticeable effect.